A New Perspective at the Ship-Air-Sea-Interface: The Environmental Impacts of Exhaust Gas Scrubber Discharge - Endres, Sonja; Maes, Frank; Hopkins, Frances; Houghton, Katherine; Mårtensson, Eva M.; Oeffner, Johannes; Quack, Birgit; Singh, Pradeep; Turner, David (Frontiers in Marine Science, 2018)
Shipping emissions are likely to increase significantly in the coming decades, alongside increasing emphasis on the sustainability and environmental impacts of the maritime transport sector. Exhaust gas cleaning systems (‘scrubbers’), using seawater or fresh water as cleaning media for sulphur dioxide, are progressively used by shipping companies to comply with emissions regulations. Little is known about the chemical composition of the scrubber effluent and its ecological consequences for marine life and biogeochemical processes. If scrubbers become a central tool for atmospheric pollution reduction from shipping, modelling and experimental studies will be necessary to determine the ecological and biogeochemical effects of scrubber wash water discharge on the marine environment. Furthermore, attention must be paid to the regulation and enforcement of environmental protection standards concerning scrubber use. Close collaboration between natural scientists and social scientists is crucial for progress toward sustainable shipping and protection of the marine environment.